Integrating Local Wisdom And Modern Technology To Address Society 5.0 Era Challenges In Culture - Fitra Zahrotul Luqmi; Erjati Abas; Istiana Istiana; Karmila Karmila (Riviera Publishing, 2025)
The Society 5.0 era presents significant challenges for the preservation of local culture in the midst of the rapid flow of modern technology. Cultural institutions are required to reorient their role in integrating local wisdom with technology to answer the needs of the digital community. This research aims to analyze the adaptation and transformation strategies of cultural institutions in the face of digital disruption, as well as identify effective integration models between traditional values and technological innovation. Using qualitative-descriptive research methods with a phenomenological approach, data were collected through in-depth interviews, participatory observations, and documentation studies from five indigenous communities in Indonesia that have successfully integrated technology in their cultural practices. The results of the study show three main findings: cultural digitalization strengthens people's cultural identity through wider access and revitalization of traditional values, technology adoption increases community socio-economic resilience through the creation of new jobs and market expansion, and the integration of traditional ecological knowledge with modern technology creates an effective sustainable development model. However, challenges such as the digital divide, cultural resistance, and intellectual property rights protection still need to be addressed. The implications of this study include the need for policies that support cultural digitalization by respecting indigenous rights, increasing digital literacy, and a cross-sectoral collaborative approach to ensure the successful integration of technology with local cultures. This research makes a strategic contribution in building a harmonious framework between cultural preservation and technological advancement, as well as supporting the creation of an adaptive society without losing its cultural identity.